2007
DOI: 10.7899/1042-5055-21.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Interns' Perceptions of Stress and Confidence

Abstract: Objective: Psychological stress has been shown to influence learning and performance among medical and graduate students. Few studies have examined psychological stress in chiropractic students and interns. This preliminary study explored interns' perceptions around stress and confidence at the midpoint of professional training. Methods: This pilot study used a mixed-methods approach, combining rating scales and modified qualitative methods, to explore interns' lived experience. Eighty-eight interns provided r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…36 Chiropractic students are known to experience similar stresses during their training program. 19,37 A post hoc analysis of our data with a 1.25 SD grouping criterion, rather than the 1 SD used by Chapell et al, 25 found a significant difference between low (mean À 1.25 SD) and high (mean þ 1.25 SD) TAI groups (p , .05; Tables 5, 6). Therefore, although we found no significant difference between the total test anxiety levels suggested by Chapell et al, 25 our post hoc analysis suggested that a new grouping criterion (1.25 SD rather than 1 SD) can demonstrate statistical differences.…”
Section: Discussionmentioning
confidence: 58%
“…36 Chiropractic students are known to experience similar stresses during their training program. 19,37 A post hoc analysis of our data with a 1.25 SD grouping criterion, rather than the 1 SD used by Chapell et al, 25 found a significant difference between low (mean À 1.25 SD) and high (mean þ 1.25 SD) TAI groups (p , .05; Tables 5, 6). Therefore, although we found no significant difference between the total test anxiety levels suggested by Chapell et al, 25 our post hoc analysis suggested that a new grouping criterion (1.25 SD rather than 1 SD) can demonstrate statistical differences.…”
Section: Discussionmentioning
confidence: 58%
“…It was shown that they did not detect stressed students even though over half the students reported having had emotional or psychological problems that interfered with their academic work. These two medical studies, alongside the research by Spegman and Herrin, 19 highlight the importance of the transitional periods from preclinical to student-clinician to eventual practitioner as being particularly stressful periods in medical and chiropractic education with the internships or preceptorships representing major components of students' daily educational experience.…”
Section: Preceptorships/internships/outreachmentioning
confidence: 99%
“…One more internship study, 19 using mixed methods, explored interns' perceptions around stress and confidence during the midpoint, which included their internship period, of their professional training. This study showed that the interns considered stress and confidence important issues, with the findings revealing inverse relationships between stress and confidence with higher stress being inversely related to lower confidence.…”
Section: Preceptorships/internships/outreachmentioning
confidence: 99%
See 1 more Smart Citation
“…11 At the same time, data from a study by Kizhakkeveettil et al 12 that uses the validated perceived stress scale (PSS-10) suggests that stress levels were not statistically significantly different across terms. Another study done by Spegman et al 13 indicates that chiropractic students experience multiple sources of stress, and this stress negatively influences student confidence levels. Also, a study among 116 chiropractic students done by Zhang et al 14 showed that students experience high levels of stress while performing an objective clinical examination, and these stress levels negatively impact their performance.…”
Section: Introductionmentioning
confidence: 99%